2010
DOI: 10.1111/j.1600-0765.2010.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphorymonas gingivalis induces intracellular adhesion molecule-1 expression in endothelial cells through the nuclear factor-kappaB pathway, but not through the p38 MAPK pathway

Abstract: The induction of ICAM-1 by infection of umbilical vein endothelial cells with P. gingivalis might be mediated through the NF-κB pathway, but not by the p38 MAPK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
3
31
1
Order By: Relevance
“…NF-κBIZ in particular demonstrated a marked 11.2-fold and 9.6-fold up-regulation, at 6 h and 24 h, respectively. The present findings are in agreement with previous studies demonstrating a central role of NF-κB in the pro-inflammatory responses to P. gingivalis in various cell types including fibroblasts, stromal cells, gingival epithelial cells, osteoblasts, cementoblasts and endothelial cells [11], [90], [93], [110][112].…”
Section: Resultssupporting
confidence: 94%
“…NF-κBIZ in particular demonstrated a marked 11.2-fold and 9.6-fold up-regulation, at 6 h and 24 h, respectively. The present findings are in agreement with previous studies demonstrating a central role of NF-κB in the pro-inflammatory responses to P. gingivalis in various cell types including fibroblasts, stromal cells, gingival epithelial cells, osteoblasts, cementoblasts and endothelial cells [11], [90], [93], [110][112].…”
Section: Resultssupporting
confidence: 94%
“…In preparation for this study, we ran experiments with MOIs of 10, 100, and 1,000 (data not shown). Results of studies using various MOIs, including the MOIs of 10 (18), 100 (19,20), and 1,000 (18), have been previously reported in the literature. The optimum concentration achieved in our experiments-in line with most publications in the literature-was the MOI of 100.…”
Section: Methodsmentioning
confidence: 89%
“…At present, several signaling pathways have been shown to be involved in osteogenesis, such as MAPKs, BMP-2-Smad and NF-κB [2123]. Among them, p38 and ERK1/2 MAPKs have been reported to be important for early osteoblast differentiation in various cell lines [24].…”
Section: Resultsmentioning
confidence: 99%